2022
DOI: 10.1097/bpo.0000000000002156
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Cost of Reduction of Overriding Pediatric Distal Radius Fractures

Abstract: Background: This study compared radiographic outcomes of pediatric patients undergoing closed reduction of 100% displaced distal radius fractures to a historical, published cohort treated with casting alone. We also examined the expense associated with sedated reduction. Methods: Single-center, retrospective cohort study examining radiographic outcomes following reduction of 100% translated distal radius fractures in 50 consecutive pediatric patients. Radiographic outcomes were compared with a historical coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…23 Savings with nonsurgical management are compounded if closed reduction and immobilization can be performed in the emergency department 24 rather than in the clinic, although conscious sedation costs can be significant. 25 Although no specific data regarding the cost of emergency department management specifically for SCH fractures is available, we do know that the costs in the emergency department vary greatly by region and by type of sedation performed, 26,27 and PHIS data demonstrates that surgical treatment of pediatric distal radius fractures results in hospital costs over 500% of nonsurgical treatment. 26 Future studies directly comparing the costs of operative fixation versus sedated reduction and casting in SCH fractures would inform this discussion dramatically.…”
Section: Discussionmentioning
confidence: 99%
“…23 Savings with nonsurgical management are compounded if closed reduction and immobilization can be performed in the emergency department 24 rather than in the clinic, although conscious sedation costs can be significant. 25 Although no specific data regarding the cost of emergency department management specifically for SCH fractures is available, we do know that the costs in the emergency department vary greatly by region and by type of sedation performed, 26,27 and PHIS data demonstrates that surgical treatment of pediatric distal radius fractures results in hospital costs over 500% of nonsurgical treatment. 26 Future studies directly comparing the costs of operative fixation versus sedated reduction and casting in SCH fractures would inform this discussion dramatically.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients who had closed reduction spent a mean time of 6.6 hours in the emergency department and had more than double the emergency department charges ($7,330) compared with patients treated with in situ casting ($3,500). Furthermore, 36 (72%) of 50 patients in the reduction group had unacceptable alignment at some point in their follow-up requiring additional manipulation or cast modification 56 . These results beg the question of why a patient should be subjected to conversion of a stable fracture to an unstable fracture, with its inherent costs and complications, if final outcomes are similar.…”
Section: Pediatricsmentioning
confidence: 99%
“…There remains unease about how best to treat patients <10 years of age with distal radial fractures that are 100% displaced and overriding, despite evidence from 2012 in favor of in situ immobilization 55 . A recent study compared a reduction and casting cohort of 50 patients 56 with a historic in situ casting cohort of 51 patients 55 . At the final follow-up, there was significantly worse angulation in the reduction group in both the sagittal plane (13.49° compared with 2.2°) and the coronal plane (8.59° compared with 0.75°).…”
Section: Pediatricsmentioning
confidence: 99%
“…We read with interest the recent publication by Bradley and colleagues. 1 In 2012 Crawford et al 2 reported that overriding extra-physeal distal radius fractures with or without ulnar fracture can be successfully treated with a moulded below elbow cast in children 10 years of age and younger. All treatments were provided by a single pediatric orthopaedic surgeon who applied the casts within 72 hours of injury, only correcting angulation, with the majority of patients having had at least one further cast change by the same surgeon.…”
mentioning
confidence: 99%
“…Crawford et al's 2 technique is more than just "casting alone" as it was simplified by Bradley et al 1 As Bradley et al 1 concluded that casting alone of off-ended distal radius fractures may be a preferable option in accordance with Crawford et al's 2 practice, we would like to ask the authors if their unit has stopped reducing the overriding of off ended distal radius fractures, if all patients are now manged with a moulded cast applied by a pediatric orthopaedic surgeon at the time of the first clinic visit to correct angulation, if they have stopped using above elbow casts and if they have shortened their casting period from a mean of 51 days to Crawford et al's 2 mean of 42 days?…”
mentioning
confidence: 99%